Добробут як імператив суспільного розвитку України - Глущенко, Ольга Вікторівна (Київ : ТОВ "Інститут суспільної трансформації", 2016)
The need for search for new scientific approaches to understanding social progress in modern science took shape in the «economics of happiness» and measuring sustainable development beyond GDP. The state of the social development of Ukraine has been considered through the prism of indicators beyond GDP and, by the results of clustering with Kohonen’s self-organising maps (SOM). There here have been distinguished five clusters by the position of the rating change: «Catastrophic Decline», «Sharp Drop», «Moderate Drop», «Almost Unchanged» and «High Growth». Ukraine is included in the «Almost Unchanged» cluster. Based on the Prosperity Index for 2015, the sub-indices of the economy and public administration of Ukraine are found to be the lowest of all the countries included in the calculation of the index. In terms of the Prosperity Index, a general profile of Ukraine as a country with poor economy, public administration, health and freedom of the individual and a satisfactory level of entrepreneurship and opportunity, education, safety, security and social capital has been defined. The author’s definition of well-being as an opportunity to meet human and community needs which contribute to their physical, spiritual, social and physical development harmonised with ethical standards and the need to preserve the environment has been offered. Well-being understood as a comprehensive depoliticised concept will allow for unification of the Ukrainian society in the conditions of conflict and controversy and ensure the transition to a sustainable improvement of the quality of life in the country.
Well-being as an imperative of Ukraine’s social development
Необходимость поиска новых научных подходов к пониманию социального прогресса в современной науке сформировалась в рамках «экономики счастья» и измерения устойчивого развития за пределами ВВП. Состояние социального развития Украины рассматривалось через призму показателей, выходящих за рамки ВВП, и по результатам кластеризации с использованием самоорганизующихся карт Кохонена (СОМ). Здесь были выделены пять кластеров по положению изменения рейтинга: «Катастрофический спад», «Резкое падение», «Умеренное падение», «Практически без изменений» и «Высокий рост». Украина включена в кластер «Практически без изменений». На основе Индекса процветания за 2015 год субиндексы экономики и государственного управления Украины оказались самыми низкими среди всех стран, включенных в расчет индекса. С точки зрения Индекса процветания, был определен общий профиль Украины как страны со слабой экономикой, государственным управлением, здравоохранением и свободой личности, а также с удовлетворительным уровнем предпринимательства и возможностей, образования, безопасности, защищенности и социального капитала. Автор предлагает определение благополучия как возможности удовлетворения потребностей человека и общества, способствующих их физическому, духовному, социальному и физическому развитию, в гармонии с этическими нормами и необходимостью сохранения окружающей среды. Благополучие, понимаемое как всеобъемлющее деполитизированное понятие, позволит объединить украинское общество в условиях конфликта и противоречий и обеспечит переход к устойчивому улучшению качества жизни в стране.
Keywords: SOCIAL SCIENCES::Business and economics::Economics; добробут; економіка щастя; за межами ВВП; Індекс Людського Розвитку; Індекс Процвітання; індекс регіонального людського розвитку; well-being; economics of Happiness; beyond GDP; Human Development Index; Рrosperity Index; integrated Index of Regional Human Development